A Karanga perspective on fertility and barrenness as blessing and curse in 1 Samuel 1:1-2:10 - Moyo, Chiropafadzo (Stellenbosch : Stellenbosch University, 2011)
Thesis (DTh)--Stellenbosch University, 2006.